The Ongoing Transformation of the Digital Public Sphere: Basic Considerations on a Moving Target - De Blasio, Emiliana (2020)
The recent decades more than anything else have revealed the ambivalence not only of the articulated expectations about the digital public sphere but also of the ‘real’ development itself. This thematic issue of Media and Communication highlights some of the criticalities and specificities of the evolution of the public sphere during this period where digital communication ecosystems are becoming increasingly central. The different articles offer a polyphonic perspective and thus contribute significantly to the debate on the transformations of the public sphere, which—in the time of the Covid-19 pandemic—dramatically affect the very essence of our democracy.